ANALYSIS OF LEXICAL COHESION - Rijal, Khairur; Sudarsono, Sudarsono; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to find out types of Lexical Cohesion Devices (LCD encountered in research background of students? theses and how often these LCD were used in theses submitted to English Language Education Study Program, Languages and Arts Education Department, Teacher Training and Education Faculty, Tanjungpura University. This research was a descriptive study. The corpus of this research consisted of ten research backgrounds of undergraduate thesis submitted to English Language Education Study Program. This research focused on reiteration. The data were sorted from the corpus by taking the vignettes that contained LCD. Of 7410 words corpus, there were 101 LCD encountered. They are 69 repetitions, 25 synonyms, and 7 hyponyms. The most frequently used LCD was repetition while the least frequently used was hyponymy. On the other hand, antonym and metonymy were not found. Besides, the research also shows that some students applied various LCD in their thesis while some others failed to use them.Keywords: Thesis Writing, Lexical Cohesion, Lexical Cohesion Devices